Development of Teaching Materials for Single Move Arts Material for Pencak Silat Extracurricular Participants - Mega Purnawati mega; Herman Afrian; Zainul Arkanudin; Hariadi Hariadi; Rina Nopiana; Suryansah Suryansah (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
This research addresses the diminishing interest and enthusiasm of students in executing solo art movements, the insufficient facilities and infrastructure for teaching these movements effectively, the declining motivation among students to practice various forms of solo art, and the inadequate comprehension of developing solo movement techniques among students. Objective. Creation of instructional resources for individual art techniques for extracurricular participants of MA.Muallimat pencak silat, innovative methodologies for students, and the provision of contemporary approaches to ensure comprehension of the standard individual art techniques of pencak silat. Materials and Methods. The study employs the Research and Development (R&D) methodology. Data gathering methodologies and equipment employ product design, data validation, and product trials. Results. The guidebook is classified as